RR Tel: MASS LOSS RATE OF THE COOL COMPONENT - Kotnik-Karuza, D.; Friedjung, M. (Одеські астрономічні публікації, 2017)
The Fe II emission lines in the optical spectrum of the symbiotic star RR Tel, observed by Crawford et al. (1999), have been analysed applying the SAC method. We obtain information about the relative populations of the lower levels of the lines and, assuming them to be in LTE, we determine the column densities of Fe+ and of H. The mass loss rate has been calculated using the mean cool component radius obtained from the bolometric properties of Mira variables with a pulsation period similar to that of the cool component of RR Tel.